Study on Coal Gangue Identification Based on Vibration and Its Adaptability to Coal-Caving Process Parameters - Lirong Wan; Jiantao Wang; Dejian Ma; Zhaoji Li; Zhenguo Lu; Zhaosheng Meng (Shock and Vibration)
The broken top coal and gangue in the fully mechanized cave mining will be released from the rear of the hydraulic support in the form of bulk. In this process, the medium properties through the coal opening can be judged by monitoring the vibration signal on the tail beam. Based on the coupling method of the discrete element method (DEM) and the finite element method (FEM) in LS-DYNA, this article simulates the whole process of coal caving, establishes the finite element model of the tail beam of hydraulic support and the discrete element model of coal gangue particles, and analyzes the influence of coal caving step distance, mining and caving ratio, and pitching angle of the mining field on the application effect of the vibration identification method. The coal caving step distance has a great influence on the recognition effect, and some bottom coal should be appropriately sacrificed to reduce the gangue content. The application effect of the vibration identification method is good under different mining and caving ratios. Downward mining can cause gangue to be released in advance, making the recognizable signal lag behind the change of gangue content, while upward mining will lose a part of the coal, but the application of vibration recognition is better than downward mining.